Model Matematika Tendangan Pisang Sepak Pojok pada Olahraga Sepakbola - tomy aprinaldi; media rosha (Journal of Mathematics UNP, 2019)
Abstract — Football is the most interest sport by the public. The problem in football is a want to many scores. Scoring on football can be from open play and set play. In this research, the authors chose to conduct a scoring research through the set play from a football corner with a banana kick technique. The purpose of this research are: Forming a mathematical modeling banana kick of corner on football, analyzing the model, and interpreting model analysis results. The banana kick math model of the football corner is a regular differential equation-shaped system. The solution of this model to use a numerical solution with the fourth order Runge-Kutta method. Then, done simulation by using matlab. Simulated results show that, with an initial velocity 29,5 m/s the ball will be goal, but with initial velocity 23 m/s and 35 m/s the ball will not goal.  Keywords — Mathematical Modeling, Banana Kick, Corner Kick.